Activation of the glmS Ribozyme Confers Bacterial Growth Inhibition. (30th January 2017) - Schüller, Anna; Matzner, Daniel; Lünse, Christina E.; Wittmann, Valentin; Schumacher, Catherine; Unsleber, Sandra; Brötz‐Oesterhelt, Heike; Mayer, Christoph; Bierbaum, Gabriele; Mayer, Günter
Abstract: The ever‐growing number of pathogenic bacteria resistant to treatment with antibiotics call for the development of novel compounds with as‐yet unexplored modes of action. Here, we demonstrate the in vivo antibacterial activity of carba‐α‐d ‐glucosamine (CGlcN). In this mode of action study, we provide evidence that CGlcN‐mediated growth inhibition is due to glmS ribozyme activation, and we demonstrate that CGlcN hijacks an endogenous activation pathway, hence utilizing a prodrug mechanism. This is the first report describing antibacterial activity mediated by activating the self‐cleaving properties of a ribozyme. Our results open the path towards a compound class with an entirely novel and distinct molecular mechanism. Abstract : Inspiring self‐destruction : CGlcN6P induces the self‐cleavage of the glmS ribozyme. This leads to degradation of the glmS mRNA and, consequently, to a reduction of the GlmS enzyme. As the enzyme is essential, this eventually causes inhibition of bacterial growth.